Pd-functionalized MCM-41 nanoporous silica as an efficient and reusable catalyst for promoting organic reactions1. Issue 21 (6th March 2015) - Nejat, Razieh; Mahjoub, Ali Reza; Hekmatian, Zahra; Azadbakht, Tahereh
<x xml:space="preserve">Abstract</x> Pd-functionalized MCM-41 nanoporous silica has been explored as an efficient and recyclable catalyst to effect Suzuki and Mizoroki–Heck cross-coupling reactions, under solvent-free conditions.